Perjuangan Masyarakat Adat untuk Keadilan Ekologis di Teluk Benoa, Bali - Slamet Subekti (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Environmental tragedy overshadows efforts to seize coastal space (Coastal and Ocean Grabbing) in part from 1,373 ha. for the Benoa Bay reclamation project in South Bali. So far, Benoa Bay has become a livelihood for fishermen and marine tourism practitioners. This water area with intertidal tides allows flushing to maintain sea water quality, in addition to the 100 ha of “Ngurah Rai” mangrove forest. which regulates hydro-orology around Denpasar. Public reasoning was disturbed when the investors of PT TWBI facilitated by the State through the Presidential Regulation, the Ministerial Decree KP and the Bali Governor's Decree planned to build 12 islands by sinking over 700 ha of water. for established hotels, villas, offices, educational facilities, sports complexes, trade, botanical gardens, apartments and floating villas. The controversy took place when the results of an AMDAL study from LPPM Udayana University stated that the Benoa Bay area was not socio-culturally suitable for reclamation, but investors sought to continue the reclamation by cooperating with a number of universities from outside Bali to conduct a comparative AMDAL study. Responding to the plan, the indigenous people through Paruman Pakraman stated their attitude to reject the reclamation of Benoa Bay by considering environmental sustainability and the preservation of customary-cultural areas. The reclamation issue of Benoa Bay in its development has not only been an environmental issue, but has penetrated into the realm of local politics. When the Bali Pilgub, Denpasar Pilwakot and Badung Pilbup and even the election of Bandesa (traditional village officials) conditioned all candidates to make an integrity pact rejecting the reclamation of Benoa Bay, including candidates who had been known to be pro-reclamation. After twice (2014-2018) the location permit was declared not meeting the AMDAL study, now investors have obtained a new permit (2018-2020) from the KKP to continue the struggle over the Benoa Bay living space. The ForBALI movement, which is the mandate of Pasubayan Pakraman, is preparing a new round of struggle for environmental justice in Benoa Bay. ForBALI's agenda going forward, first: push the results of the AMDAL study to be socio-culturally inappropriate. Second, submit a review of Perpres No. 51/2014 which is the